Puritans, Nuns and Love: Reflections on L. M. Alcott and Mary E. Wilkins Freeman - Aušra Paulauskienė (European Journal of American Studies)
Despite their artistic and generational differences, Louisa May Alcott and Mary E. Wilkins Freeman subscribe to the new, revivalist evangelical, understanding of marital love in their critique of the Puritan view of love and marriage. In A Marble Woman (1865) and Work: A Story of Experience (1873), Alcott defines love as an involuntary attraction and sees it as the only reason for marriage. In Pembroke (1894) and the early short fiction, her younger New England compatriot, Freeman, echoes the idea that it is better to remain a metaphorical nun than marry for any other reason but mystical love. In an absence of a God-given mate, female protagonists transform their love to compassionate care. On the other hand, in the texts of both writers, most male characters battle the vestiges of Puritan will before succumbing to the unguarded expression of romantic love, usually in dramatic conversion-like transformations.